EFFECT OF SOCIAL CAPITAL ON PRODUCTIVITY OF CASSAVA FARMERS IN IJEBU NORTH EAST LOCAL GOVERNMENT AREA OF OGUN STATE, NIGERIA - Balogun, Olubunmi Lawrence; Ogunsina, Ifeoluwa Josef; Ayo-Bello, Taofeek Ayodeji; Afodu, Osagie John (Journal of Agricultural Sciences (Belgrade), 2018)
Nigeria is an agriculturally labor-intensive economy and the protection and utilization of the labor resource to guarantee highest productivity is of immense vitality to the growth of the agricultural sector. This study assessed the relationship between social capital and productivity of cassava farmers in Ijebu North-East local government area of Ogun state. Purposive sampling procedure was employed in the study. Data were collected from one hundred and thirty nine cassava farmers by the use of well-structured questionnaire. Data were analyzed using descriptive statistics, total factor productivity and ordinary least squares model. Mean age and household size of cassava farmers were 44.2±9.9 years and 6.0±3.1 respectively. Density of memberships in associations was 2.7±1.3. The average meeting attendance index by farmer was three out of four meetings (77.2%). Membership\ of the association was moderately diversified with heterogeneity index of 59.2% and farmers participated in one out of four decision making processes of their associations. Monthly cash contribution of farmers to associations was low (N132.04±N107.67) and trust index was 0.296. Farmers cultivated an average of 1.25 ha with total factor productivity of 0.096Kg/₦. Result shows that age of farmer, age squared (life cycle), household size, farm size, cash contribution and decision making significantly determined productivity of cassava farmers in the study area. Social capital significantly influenced cassava farmers’ productivity. It is therefore suggested that policy makers interested in improving the living conditions of farmers and their production output should make active participation in local level institutions compulsory.Social capital, productivity, agricultural sector, cassava farmers, Nigeria